Streptococcus pyogenes proteins involved in resistance to antimicrobial peptides - Shahdan, Intan Azura; Hall, Judith; Kehoe, Mike (2010)
S. pyogenes secrete a large array of molecules that might contribute to resistance against the human’s antimicrobial peptides (AMPs). Some of these are anchored in the cell-wall by enzymes called sortases and others are released from the cell after secretion. Two released proteins that have previously been reported to inhibit bactericidal effect of the AMPs are streptococcal inhibitor of complement (SIC) and cysteine protease, SpeB. In this study, several S. pyogenes strain SF370 deletion mutants were compared to the parent wild-type strain for resistance to the AMPs LL-37 and LEAP-2. We found that released proteins SIC and SpeB contribute to streptococcal resistance against LL-37; and cell wallanchored proteins by sortases SrtA and SrtC are also important in streptococcal resistance against LL-37 but not with LEAP-2. Our study conclude that LL-37 kills S. pyogenes strain SF370 better than LEAP-2 peptide.